Rare tibioperoneal trunk aneurysm diagnosed in a pregnant patient that was successfully treated with an open bypass following a spontaneous abortion - Richard Tan, MBBCh; Bongseok Jung, BS; Tej Sura, MD; Gregg Landis, MD; Yana Etkin, MD; Larry Frankini, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
Tibioperoneal (TP) trunk aneurysms are rare with limited cases reported in the literature. We present a unique case of an idiopathic TP aneurysm in a pregnant patient who was treated after a spontaneous complete abortion. The patient had no history of trauma, infection, or prior surgeries. The aneurysm was repaired successfully with an open interposition TP trunk bypass using the greater saphenous vein as a conduit. The patient recovered well with intact pulses and was discharged on postoperative day 2 with no complications.